Islamic Religious Education Teacher Strategy in Improving the Quality of Islamic Religious Education Learning at Muhammadiyah High School, Magelang Regency - Wibowo, Wahyu Ari; Mawardi , Imam; Imron, Imron (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to determine the application of Islamic Religious Education Teacher Strategies in Improving the Quality of Islamic Religious Education Learning in Muhammadiyah High Schools in Magelang Regency starting from planning, implementing and evaluating Teacher Strategies, supporting and inhibiting factors and efforts made by teachers to improve the quality of PAI learning. The research subjects were PAI teachers and students. The research object is the Strategy of Islamic Religious Education Teachers in Muhammadiyah High School, Magelang Regency, the research indicators are Teacher Strategy, supporting and inhibiting factors and efforts made by teachers to improve the quality of PAI learning. The data collection techniques used are: Observation, interviews, documentation studies. Meanwhile, data management analysis techniques consist of: data compression, data reduction, data display/presentation, data analysis, increasing the validity of results and drawing conclusions. Results The results of the research show that PAI teachers' internal strategies improve the quality of Islamic religious education teaching at Muhammadiyah Magelang High School. The efforts implemented to improve the quality of Islamic religious education learning are, namely 1). Improving the quality of student education Islamic religious education topic 2). Obtain instructions or literature on Islamic religious education subjects, 3). Craftsmanship teaching methodology for teachers in teaching Islamic subjects